IMPLEMENTATION OF WHISTLEBLOWING SYSTEM: GOOD CORPORATE GOVERNANCE, FUNDAMENTAL FACTORS, COMPANY RISK AND INVESTOR REACTION - Gita Claudia; Theresia Dwi Hastuti; Stefani Lily Indarto (Department of Accounting, Faculty of Economics, Universitas Sriwijaya, 2023)
One of the influencing factors for the implementation of this policy in Indonesia is the emergence of several cases of fraud that occurred in large companies in this country. The urgency of this research is (1). The implementation of the whistleblowing system in Indonesia is still a growing polemic, so many companies have not fully implemented this system. This research is a development of research conducted by Sulhani and Wardani (2017) with the addition of variables. The conclusion in this research is that the variables of the audit committee and internal audit have an effect on the implementation of the whistleblowing system. Meanwhile, the variables of board of commissioners, internal control system, managerial ownership, company risk, company size, and investor reactions have no effect on the implementation of the whistleblowing system. it can be seen that audit process has an influence on the implementation of the whistleblowing system.